HISTORICAL AND LEGAL NATURE OF ADMINISTRATIVE OFFENCE (MISDEMEANOR) AND ADMINISTRATIVE JUSTICE IN UKRAINE - Borodin, Ivan; Rybikova, Ganna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to define of legal regulation of the institute of administrative responsibility in the context of which it is important to understand the administrative offense (misdemeanor) and the institute of administrative justice. Research methods: phenomenological, hermeneutic; sociological; logical; dialectical methods are used in the article. Results: knowledge of an administrative offense (misdemeanor) as a type of legal liability and the institution of administrative justice as legal phenomena in accordance with the fundamental standards of society, state and law, in their interconnection. Discussion: the historical aspect of legal regulation of administrative offenses and administrative justice in Ukraine is analyzed, as a result of which the opinion is substantiated that the institution of administrative justice in Ukraine in its formation originates in the Russian Empire, continues to develop in the Soviet Union, and then in Ukraine, we believe that this institution is one of the most relevant areas of building a legal state in Ukraine. The analysis of the formation and development of the institution of administrative justice in Ukraine suggests that the theory and practice of judicial control followed the path of gradual expansion of the competence of general courts to resolve administrative disputes. The idea of creating a system of administrative justice was hindered by ideological dogmas and stereotypes prevailing in the totalitarian state, which was accompanied by the justification of the impossibility of introducing this institution for a number of reasons, including the threat of a significant expansion of the state apparatus etc. Ukraine has inherited from the Soviet Union a system in which administrative disputes fall under the jurisdiction of general courts and are considered according to the rules of civil proceedings, while other disputes are considered in an instance procedure in compliance with the rules of administrative procedure.